2023
DOI: 10.1039/d2nr06469c
|View full text |Cite
|
Sign up to set email alerts
|

Optimized coaxial focused electrohydrodynamic jet printing of highly ordered semiconductor sub-microwire arrays for high-performance organic field-effect transistors

Abstract: Patterning of semiconductor polymers is pertinent to preparing and applying organic field-effect transistors (OFETs). In this study, coaxial focused electrohydrodynamic jet printing (high resolution, high speed, and convenient) was used...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This method consists of the reduction of a metal salt onto the surface of the NMs such as silica coatings or magnetic beads. The NPs produced can be varied in materials and morphology, [76] depending on the reduction conditions. Finally, the direct use of nanoparticles as nanomotors has been reported to yield significant advances within the field, NMs made of Au@Ag core-shell nanorods (NRs) have been proposed for the detection of explosives.…”
Section: Fabrication Of Nms With Noble Metal Surfaces For Sers Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…This method consists of the reduction of a metal salt onto the surface of the NMs such as silica coatings or magnetic beads. The NPs produced can be varied in materials and morphology, [76] depending on the reduction conditions. Finally, the direct use of nanoparticles as nanomotors has been reported to yield significant advances within the field, NMs made of Au@Ag core-shell nanorods (NRs) have been proposed for the detection of explosives.…”
Section: Fabrication Of Nms With Noble Metal Surfaces For Sers Sensingmentioning
confidence: 99%
“…For example, it has been demonstrated that up-and-down oscillations in 3D space can also facilitate molecular enrichment. [76] 3.3. NMs-Driven SERS Applications SERS applications may be broadly divided into detection and imaging.…”
Section: Effects Of the Motion For Nm-driven Sersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ITO electrodes have limited their application in flexible devices due to the poor mechanical strength of the material itself, the complexity of the preparation process, and the high cost. Recently, many conductive materials including conductive polymers, , carbon-based materials, and conductive metal-based materials have been developed as flexible alternatives to ITO, among which conductive polymers and carbon-based materials are poor in electrical conductivity, light transmission, and environmental stability. PEDOT:PSS is a typical conductive thin-film material with a variety of advantages, including high optical transparency, excellent flexibility, and superior chemical stability.…”
Section: Introductionmentioning
confidence: 99%